Patient-derived breast model repository, a tool for hyperthermia treatment planning and applicator design. (31st December 2022) - Androulakis, Ioannis; Sumser, Kemal; Machielse, Melanie N. D.; Koppert, Linetta; Jager, Agnes; Nout, Remi; Franckena, Martine; van Rhoon, Gerard C.; Curto, Sergio
Abstract: Objective: The addition of hyperthermia in the treatment of intact breast cancer with the aim to improve local response is currently in a research phase. First, optimal hyperthermia devices need to be developed, for which a diverse, anatomically and pathologically accurate set of patient models is necessary. Methods: To investigate the effects of inter-subject variations on hyperthermia treatment plans, we generated a repository of 22 anatomically and pathologically diverse patient models based on MR images of breast cancer patients. Hyperthermia treatment plans were generated for the 22 models using a generic theoretical phased array hyperthermia applicator. Results: Good temperature coverage was achieved in the vast majority of the models, with median values for T 10 = 43.5°C (41.9–43.8°C), T 50 = 42.5°C (41.3–43.3°C), and T 90 = 41.3°C (39.8–42.6°C) under the condition that the maximum temperature increase in the patient is limited to 44°C. Conclusions: For future development of hyperthermia devices and treatment methods, a repository with a sufficiently large number of representative patient models, such as the one provided in this study, should be used to ensure applicability to a wide variety of patients. This repository is therefore made publicly available.